Prevalence of Cefepime-Resistant Escherichia coli in Iran: A Meta-Analysis (2007-2016) - Seyyede Maryam BECHASHK; Ghobad MORADI; Behzad MOHSENPOUR; Rashid RAMAZANZADEH (Tehran University of Medical Sciences, 2019)
Background: Cefepime-resistant Escherichia coli (E. coli) is one of the seven important types of microbial resistance. This meta-analysis study was conducted to identify the prevalence of cefepime-resistant E. coli in Iran during 2007-2016. Methods: Studies published were searched in Persian databases (including Magiran, and SID) and international databases (including PubMed, ScienceDirect, and Scopus). The selected studies included all types of laboratory methods. Moreover, the random effects model (DerSimonian Laird method) was used to addresses the high heterogeneity (50% < I2) between the reviewed studies. The collected data were categorized into different subgroups on the basis of the year of study and province. Data analysis was performed using the Statsdirect software. Results: Overall, 516 articles were selected from the searched medical databases. After reviewing and applying the inclusion criteria, irrelevant papers were excluded and the remaining 26 studies were meta-analyzed. The overall prevalence of cefepime-resistant E. coli was 53.42% (95%: 43.35, 63.35), ranging from 25% (95%CI: 21.67, 28.55) in 2009 to 61.95% (95%CI: 56.62, 67.09) in 2016. Conclusion: The prevalence of cefepime-resistant E. coli in Iran has had an increasing and alarming trend during the recent years. Therefore, it is necessary to use practical strategies and interventions to control and monitor cefepime-resistant E. coli in the country.